Monitoring of the mammal fauna by studying owl pellets: a case of small mammals in protected areas of Podillia - 10.15407/TU2404 (Theriologia Ukrainica, 2022)
Using owl pellets analysis to monitor mammals in protected areas makes it possible to accumulate a unique material to study the distribution and relative abundance of both common and rare species. Due to the ease of collecting and accumulating of pellets, this method helps to quickly obtain a large amount of material to monitor the changes in natural areas and objects during certain time intervals without interfering with the course of natural processes. The proportions of small-mammal species in the diet of most owls are representative of the proportions of species in their groups. Therefore, the pellet method can be used to organise monitoring of mammal species of natural regions. We analysed nearly 2000 pellets of several species of owls collected in Podillia in the course of the study. Pellets are mostly collected within protected areas. Small mammals form the basis of the diet of the studied species of owls. The diet of the short-eared owl is the most diverse, and it includes 18 species of small mammals. The common vole occurs the most often. The diet of other owl species is also diverse, in particular of the little owl, tawny owl, and eagle owl. As in the case of the short-eared owl, the main prey of the barn owl and grey owl is a common species—the common vole. The diet of the eagle owl, unlike others, is dominated by larger small-mammal species—brown rat, white-breasted hedgehog, and European hamster. In addition to common species, the analysis of owl pellets allows us to identify not only the most common, but also rare species, such as the European hamster, bicoloured shrew, lesser white-toothed shrew, and various bats. Therefore, the pellet method of research is highly effective in analysing the composition of the fauna and the structure of communities, of both prey and predator species. Owl pellet analysis is a valuable asset during small-mammal monitoring studies, and is especially useful for sampling of indicator small-mammal species during environmental impact assessments in protected areas. The method has considerable advantages compared to standard survey methods of small mammals— it does not require the removal of animals from the natural environment, which makes it relevant for use in protected areas.